Growth and Decay Behaviour of a Sawtooth Profile in Non-Ideal Gas - Singh R.; Singh L.P. (My University, 2025)
In the present paper, the progressive wave approach is used to analyze the main features of weakly nonlinear waves propagating in a non-ideal gas. An evolution equation, which characterizes the wave process in the high frequency domain and points out the possibility of wave breaking at a finite time, is derived. Further, we consider a sufficiently weak shock at the outset and study the propagation of the disturbance given in the form of a sawtooth profile. The effect of non-idealness on the formation of shock with planar and cylindrical symmetry is analyzed. © 2015, Springer India Pvt. Ltd.